Radiation protection in medical radiography - Statkiewicz-Sherer, Mary Alice, 1945-; Visconti, Paula J.; Ritenour, E. Russell, 1953-; Haynes, Kelli (Kelli Welch) (Maryland Heights, MO : Elsevier/Mosby, 2014)
A full-color resource, Radiation Protection in Medical Radiography, 7th Edition makes it easy to understand both basic and complex concepts in radiation protection, biology, and physics. Concise coverage promotes the safe use of ionizing radiation in all imaging modalities, including the effects of radiation on humans at the cellular and systemic levels, regulatory and advisory limits for human exposure to radiation, and the implementation of radiation safety practices for patients and personnel. This edition includes new content on the impact of radiation levels during the nuclear power plant crisis that followed the 2011 earthquake/tsunami in Japan. From an author team led by well-known radiation protection expert Mary Alice Statkiewicz Sherer, this text has consistently helped students perform well on the ARRT exam.
Introduction to radiation protection -- Radiation : types, sources, and doses received -- Interaction of x-radiation with matter -- Radiation quantities and units -- Radiation monitoring -- Overview of cell biology -- Molecular and cellular radiation biology -- Early deterministic radiation effects on organ systems -- Late deterministic and stochastic radiation effects on organ systems -- Dose limits for exposure to ionizing radiation -- Equipment design for radiation protection -- Management of patient radiation dose during diagnostic x-ray procedures -- Management of imaging personnel radiation dose during diagnostic x-ray procedures -- Radioisotopes and radiation protection.
Includes bibliographical references and index.
Keywords: Radiography, Medical -- Safety measures; Radiation Protection -- methods; Radiography -- adverse effects; Radiation Monitoring -- methods; Radiation Effects; Radiography, Medical -- Safety measures; Medizinische Radiologie; Strahlenschutz